Ottawa 2020 consensus statements for programmatic assessment – 2. Implementation and practice. (3rd October 2021) - Torre, Dario; Rice, Neil E.; Ryan, Anna; Bok, Harold; Dawson, Luke J.; Bierer, Beth; Wilkinson, Tim J.; Tait, Glendon R.; Laughlin, Tom; Veerapen, Kiran; Heeneman, Sylvia; Freeman, Adrian; et al.
Abstract: Introduction: Programmatic assessment is a longitudinal, developmental approach that fosters and harnesses the learning function of assessment. Yet the implementation, a critical step to translate theory into practice, can be challenging. As part of the Ottawa 2020 consensus statement on programmatic assessment, we sought to provide descriptions of the implementation of the 12 principles of programmatic assessment and to gain insight into enablers and barriers across different institutions and contexts. Methods: After the 2020 Ottawa conference, we surveyed 15 Health Profession Education programmes from six different countries about the implementation of the 12 principles of programmatic assessment. Survey responses were analysed using a deductive thematic analysis. Results and Discussion: A wide range of implementations were reported although the principles remained, for the most part, faithful to the original enunciation and rationale. Enablers included strong leadership support, ongoing faculty development, providing students with clear expectations about assessment, simultaneous curriculum renewal and organisational commitment to change. Most barriers were related to the need for a paradigm shift in the culture of assessment. Descriptions of implementations in relation to the theoretical principles, across multiple educational contexts, coupled with explanations of enablers and barriers, provided new insights and a clearer understanding of the strategic and operational considerations in the implementation of programmatic assessment. Future research is needed to further explore how contextual and cultural factors affect implementation.